Power-off static stability analysis of a clean configuration of a hybrid buoyant aircraft - Ul Haque, Anwar; Asrar, Waqar; Sulaeman, Erwin; Syed Mohamed Ali, Jaffar; Omar, Ashraf Ali (2015)
In the present study, the static stability of a hybrid buoyant aircraft is estimated using a panel method to solve the potential flow about the aircraft’s components other than the voluminous fuselage. A viscous flow solver was used to compute the flow over the fuselage to obtain the stability coefficients. A combination of the results of the two solutions was used to determine the aerodynamic characteristics of the aircraft under cruise conditions. An interesting effect of anhedral angle on overall zero lift pitching moment was observed and was correlated with a marine animal’s anatomy. Estimated position of neutral point is consistent with the earlier work of Munk-Multhopp. An option of multiple vertical tails is proposed to improve the lateral stability on the ground. Results so far obtained show that the proposed configuration with three lifting surface and twin vertical tails exhibit good stability characteristics. However, there is a need to investigate the aerodynamic and stability behavior through wind tunnel testing.